Some Fundamental Problems in Becker, Grossman and Murphy's Implementation of Rational Addiction Theory - Knut R. Wangen (Statistics Norway, Research Department, 2004)
The econometric implementation of rational addiction theory has been highly influenced by Becker, Grossman and Murphy (BGM). They specify an Euler equation where current consumption is determined by current price and past and future consumption. This model is claimed to be able to discriminate between rational addictive, myopic addictive, and non-addictive behavior. However, as demonstrated in this paper, the coefficients of the Euler equation are not structural parameters. Provided that two implausible assumptions do not hold, the Euler equation coefficients for the rational addict are shown to be non-constant. But even when these assumptions are assumed to be valid, the coefficients of the Euler equation will vary under the alternative hypothesis of myopic addiction. Moreover, and in contrast to the common interpretation, BGM's non-addicted consumer is influenced by past consumption, implying that a rational and a myopic non-addict behave differently. These problems makes it unclear how analyses based on the BGM approach can support, or reject, rational addiction theory.
Keywords: D11; D12; I10; 330; Rational addiction; Euler equation